2012
DOI: 10.1103/physrevb.86.014420
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of spin pairs to the magnetic response in a dilute dipolar ferromagnet

Abstract: We simulate the dc magnetic response of the diluted dipolar-coupled Ising magnet LiHo0.045Y0.955F4 in a transverse field, using exact diagonalization of a two-spin Hamiltonian averaged over nearest-neighbour configurations. The pairwise model, incorporating hyperfine interactions, accounts for the observed drop-off in the longitudinal (c-axis) susceptibility with increasing transverse field; with the inclusion of a small tilt in the transverse field, it also accounts for the behavior of the off-diagonal magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Magnetic dilution is a useful approach to investigate the magnetic properties of a given SMM without the influence of its magnetic neighbors . Once crystallized in an isomorphous diamagnetic matrix, the SMM behavior is generally optimized as intermolecular interactions that are likely to create additional and damaging pathways for the magnetic relaxation are suppressed .…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic dilution is a useful approach to investigate the magnetic properties of a given SMM without the influence of its magnetic neighbors . Once crystallized in an isomorphous diamagnetic matrix, the SMM behavior is generally optimized as intermolecular interactions that are likely to create additional and damaging pathways for the magnetic relaxation are suppressed .…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that transverse fields H t applied to LiHo Consistent with classical pinning, the initial softening effect is visible only when cooling in field from high temperature, whereas the high transverse field (2 kOe) hardening is historyindependent and therefore consistent with H t -induced quantum speedup. be probed directly (28,40).…”
Section: Resultsmentioning
confidence: 99%
“…The field scale H c can be connected to the microscopic properties of Li(Ho,Y)F 4 by comparison with an exact diagonalization of the full Hamiltonian for a pair of coupled Ho 3+ atoms 37 , where there is a crossing of the lowest coupled electronuclear levels for nearest-neighbor spins positioned in the ab plane at (100) or (010) relative to each other. The effects of these pairwise level crossings can be seen in the measured linear longitudinal susceptibility χ zz ( H t ) 24,37 . The characteristic dynamics of the pairwise susceptibility shift as a function of classical (temperature) and quantum-mechanical (transverse field) energy scales, moving from 9 kOe at 70 mK to 5 kOe at 150 mK.…”
Section: Discussionmentioning
confidence: 99%